Universities as innovation systems: A crucial key to sustainable national innovation policies and capacity building in Malaysia and elsewhere? - Richards, Cameron; Shahbazim, Masoomeh (2013)
In a fast-changing world where various forms knowledge have become the standard for economic value, national innovation policies have become de rigeour to explain current realities or make varying projections of the future. National innovation plans or strategies are generally focused on the policy nexus between governments and business (or 'industries' more widely).However, with 'research and development' a central indicator of innovation performance, universities are typically regarded as an important foundation for innovation capacity-building as well as theories and policies.Universities inevitably produce the graduates who directly contribute to high end economic and technological innovation and associated economic imperatives.Yet in Malaysia as in many other countries, there is relatively little industry-university collaboration and typically governments and private sector organisations complain that universities are not producing graduates with the innovative-readiness generic skills and attitudes thought to be crucial for improved national competitiveness in the global information society and knowledge economy.In the context that universities are universally regarded as crucial key to national innovation plans and strategies, this paper will look at the related dilemmas, challenges, and also opportunities of not only viewing universities as potential 'innovation systems' but actually trying to innovate and transform particular universities.